Cytotoxic effects of mercury, cadmium, lead and zinc on acanthamoeba castellanii - Mat Amin, Nakisah; Velamuthu, Rainee; Mohd. Shazili, Noor Azhar (2006)
Acanthamoeba spp are single-cell organisms that are commonly encountered in aquatic and terrestrial ecosystems. Their role in our natural environment is mainly as bacterial consumer although some of them can become pathogens and infect humans and animals. Heavy metals such as mercury, cadmium, lead and zinc are dangerous pollutants and often its dissolved form enters the aquatic environment and affects the organisms in the food web of aquatic ecosystem including amoebae. A study on the cytotoxic effect of mercury, cadmium, lead and zinc on Acanthamoeba castellanii was conducted in order to understand more about their toxicity on the amoeba by looking at their EC50 and effect on the amoeba cell morphology. The results of this study indicated that mercury is the most toxic metal since its EC50 is only 2.0 ppm, followed by Cd (13.4 ppm), Pb (23.8 ppm) and Zn (143.3 ppm). The amoeba cells were observed to be smaller in size and stained orange with AOPI indicating the cells lost its cell membrane integrity which eventually lead to the cell death by necrosis when being exposed to the heavy metals.